2019
DOI: 10.3897/phytokeys.128.35842
|View full text |Cite
|
Sign up to set email alerts
|

Systematic relevance of pollen morphology in tribe Hylocereeae (Cactaceae)

Abstract: Hylocereeae is one of the nine tribes in the subfamily Cactoideae (Cactaceae), for which the limits and recognition of genera have been controversial. Essentially, this group comprises epiphytic and hemiepiphytic genera with stems modified as climbing structures. The aim of this paper is to examine pollen attributes in representative species of genera of Hylocereeae, focusing on Selenicereus whose current circumscription comprises Hylocereus and three Weberocereus species, to find whether significant potential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Por las variables peso y °Brix, tres accesiones cumplen con los requisitos para ser sembradas comercialmente, sin embargo es necesario evaluar una modificación en las labores de cultivo para tratar de aumentar el tamaño de los frutos. T he genus Hylocereus belongs to the Cactaceae family, and recently was included in Selenicereus group (Korotkova et al, 2017); however, other authors suggest that it is important to evaluate morphological, ecological, and molecular traits to support the group position (Ruiz-Domínguez et al, 2019). In Selenicereus, there are native hemiepiphyte species from the American tropical regions considered valuable for their fruits.…”
mentioning
confidence: 99%
“…Por las variables peso y °Brix, tres accesiones cumplen con los requisitos para ser sembradas comercialmente, sin embargo es necesario evaluar una modificación en las labores de cultivo para tratar de aumentar el tamaño de los frutos. T he genus Hylocereus belongs to the Cactaceae family, and recently was included in Selenicereus group (Korotkova et al, 2017); however, other authors suggest that it is important to evaluate morphological, ecological, and molecular traits to support the group position (Ruiz-Domínguez et al, 2019). In Selenicereus, there are native hemiepiphyte species from the American tropical regions considered valuable for their fruits.…”
mentioning
confidence: 99%
“…Burelo-Ramos et al (2009) gives an example where pollen morphology can still provide additional characters to evaluate possible monophyletic groups within a complex of species, which might support some of the genera currently included in Pithecocteniinae (Bignoniaceae). Ruíz-Domínguez et al (2019) found seven pollen morphological attributes (five qualitative and two continuous) in the tribe Hylocereeae (Cactaceae) that exhibited useful variation. Brevicolpate pollen grains were shared by Kimnachia ramulosa and Pseudorhipsalis amazonica.…”
mentioning
confidence: 99%
“…The pollen terminology used was from Erdtman (1954Erdtman ( , 1969, Wagenitz (1955), Faegri and Iversen (1975), Punt et al (2007), Punt and Hoen (2009), Yurtseva et al (2014), Halbritter et al (2018) , and Ruiz-Domínguez et al (2019.…”
Section: Terminologymentioning
confidence: 99%
“…Measurements were made using Kameram 21 software based on at least 30 or more pollen grains from each specimen. The apocolpium (t) measurements was done according to Ruiz-Domínguez et al (2019) and amb dimensions was done according to Erdtman (1969).…”
Section: Microscopic Studiesmentioning
confidence: 99%